The Effect Of Efficiency And Quality Of Electronic Medical Record Services On Employee Satisfaction At Hospital X - Wening Palupi Dewi; Heni Mei Ekasari (Master of Public Health Program Universitas STRADA Indonesia, 2026)
Electronic medical records (EMR) is the use of information technology equipment to collect, store, process, and access data stored in patient medical records at a hospital in a database management system that combines various medical data sources. The purpose of this study was to determine the relationship between the efficiency and quality of electronic medical records services and the job satisfaction of service quality officers at Hospital X, Kediri City. This study uses a quantitative method with a correlational approach. The population of this study was 110 people calculated using Krejcie and Morgan and resulted in 86 people. The X variables of this study are EMR Efficiency and Service Quality while the Y variable in this study is Officer Performance. The instrument used was a questionnaire, and the data were analyzed using multiple linear regression tests. The research variables are HR quality, motivation, and officer performance. The results of this study obtained a regression equation formed is Y = 7.052 + 0.071X1 + 0.606X2. In addition, the coefficient of determination test value of 68.6% of officer job satisfaction is influenced by the variables of RME efficiency and service quality. While the remaining 31.4% is influenced by other variables, which are not within the scope of the researcher's research. These results indicate that RME Efficiency and Service Quality influence Officer Performance.